Rethinking editorial management and productivity in the COVID-19 pandemic - Quan-Hoang Vuong; Manh-Toan Ho (European Science Editing)
The indirect costs of the COVID-19 pandemic, specifically extended work absenteeism and possible loss of productivity, are discussed focusing on the research community and its publishing. We suggest that the community should learn strategic and innovative decision-making as well as crisis management from business management to think ahead, especially about working effectively and being productive in times of crisis. The main challenges are:1) communicating scientific and credible information about the pandemic,2) focusing on being productive to provide some certainty, and3) adopting a new mindset and being open to unexpected opportunities.